The Health related Quality of Life of Puerto Ricans during Cancer Treatments; A Pilot Study - Gonzalez, Velda J.; McMillan, Susan; Pedro, Elsa; Tirado-Gomez, Maribel; Saligan, Leorey N. (Puerto Rico Health Sciences Journal, 2018)
Objective: To examine the health related quality of life (HRQOL) experienced by 79 Puerto Rican adults during cancer treatments. Methods: This study used a descriptive, cross-sectional design. Participants completed a demographics form and the Functional Assessment of Cancer Therapy-General QOL questionnaire (FACT-G). Descriptive statistics were generated. Results: Participants were ages 28-78; most of the participants had breast (38.0%), prostate (14.0%) and cervical and ovarian cancers (10.1%) treated with chemotherapy (45.6%). The participants had a mean total score on the FACT-G of 75.2 (SD = 18.9). As a group, the functional well-being was the most affected (mean 17.2, SD 6.8), and the Social/Familial was the least affected (mean 20.7, SD 6.0). Conclusion: Cancer is the leading cause of death in the island of Puerto Rico. Female Puerto Rican cancer patients in this study sample had increased risk for experiencing worse: overall HRQOL, physical well-being and emotional well-being compared to males. Given that the Hispanic oncology population does not always report symptoms, risking under-assessment and under management, this suggests there may be a greater need for HRQOL surveillance for this population.